Proposed steps to develop Corporate Social Responsibility reporting - Zapciu (Niculescu), Miruna; HURDUZEU, Gheorghe (IJRDO - Journal of Business Management, 2018)
Corporate Social Responsibility is a growing concept, both in terms of research and in terms of information based on quantitative and qualitative primary data.Most of the information on Corporate Social Responsibility and Sustainable Development in Romania's business scene comes from studies and reports from private organizations (companies that have their own production or consulting companies) or non-governmental organizations, or reports from their work in the field of projects with European funding.The paper synthesizes an easy reporting procedure that complies with the latest GRI 4 (Global Reporting Initiative) standards